2006
DOI: 10.1556/aphysiol.93.2006.2-3.4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of magnesium supplementation on lactate levels of sportsmen and sedanter

Abstract: This study was performed to assess how magnesium supplementation affects plasma lactate levels at rest and exhaustion in sportsmen and sedentary. Research was performed on 30 healthy subjects varying between 18-22 years of age for a four-week period. Subjects were separated into 3 groups: Group 1; sedentary taking magnesium supplementation only (10 mg/kg/day) (Mg + S), Group 2; subjects magnesium supplemented + training 90-120 min 5 days a week (Mg + Training), Group 3; training 90-120 min 5 days a week. Lacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…14 In adjusted analyses, including measurement of comorbidities, illness severity, blood pressure, and renal function, hypomagnesemia remained a significant predictor of lactic acidosis. Although lactic acidosis in critical illness is often assumed to reflect tissue hypoperfusion in response to a low-flow state and used to direct fluid resuscitation strategies, our analyses suggest that magnesium concentrations are an additional independent predictor.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…14 In adjusted analyses, including measurement of comorbidities, illness severity, blood pressure, and renal function, hypomagnesemia remained a significant predictor of lactic acidosis. Although lactic acidosis in critical illness is often assumed to reflect tissue hypoperfusion in response to a low-flow state and used to direct fluid resuscitation strategies, our analyses suggest that magnesium concentrations are an additional independent predictor.…”
Section: Discussionmentioning
confidence: 94%
“…12 In the absence of magnesium, disrupted oxidative phosphorylation shifts toward anaerobic metabolism, resulting in lactic acid production. Magnesium infusion attenuates lactate production during surgical procedures 13 and intense physical exercise, 14 but little information exists on the association of magnesium and lactate concentrations in the critically ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…Data from animal studies suggest that magnesium might improve exercise performance via enhancing glucose availability in the brain, muscle and blood, and reducing/delaying lactate accumulation in muscles, which may delay exhaustion [115]. The positive impact on lactate has been observed in a controlled clinical study where magnesium supplementation (10 mg/kg body weight/day) for 4 weeks attenuated the exercise-induced increase in plasma lactate levels of 30 young Tae-Kwan-do sportsmen [139].…”
Section: Supplementation With Iron and Magnesium And Physical Fatiguementioning
confidence: 98%
“…Physiological indices have been used as the proxy measures of exercise performance [ 28 , 29 , 36 , 37 , 38 , 39 ]. For example, in one randomized controlled trial [ 40 ], the researchers randomly divided 30 healthy individuals (aged 18–22 years) into three groups: (1) Mg supplementation group; (2) Mg supplementation + Tae-Kwan-Do training group; and (3) Tae-Kwan-Do training group. After a 4-week intervention, the results indicated that Mg supplementation improved exercise performance, measured by a 20 m shuttle run test, through decreasing the accumulation of lactate, which was consistent with the findings from animal studies [ 18 , 26 , 27 , 32 , 33 ].…”
Section: The Association Between Mg and Exercise Performancementioning
confidence: 99%